NC-6301, a polymeric micelle rationally optimized for effective release of docetaxel, is potent but is less toxic than native docetaxel in vivo - Harada, Mitsunori (Dove Medical Press, 2012)
Drug release rate is an important factor in determining efficacy and toxicity of nanoscale drug delivery systems. However, optimization of the release rate in polymeric micellar nanoscale drug delivery systems has not been fully investigated. In this study NC-6301, a poly(ethylene glycol)-poly(aspartate) block copolymer with docetaxel (DTX) covalently bound via ester link, was synthesized with various numbers of DTX molecules bound to the polymer backbone. The number of DTX molecules was determined up to 14 to achieve an optimal release rate, based upon the authors’ own pharmacokinetic model using known patient data. Efficacy and toxicity of the formulation was then tested in animals. When administered three times at 4-day intervals, the maximum tolerated doses of NC-6301 and native DTX were 50 and 10 mg/kg, respectively, in nude mice. Tissue distribution studies of NC-6301 in mice at 50 mg/kg revealed prolonged release of free DTX in the tumor for at least 120 hours, thus supporting its effectiveness. Furthermore, in cynomolgus monkeys, NC-6301 at 6 mg/kg three times at 2-week intervals showed marginal toxicity, whereas native DTX, at 3 mg/kg with the same schedule, induced significant decrease of food consumption and neutrophil count. NC-6301 at 50 mg/kg in mice also regressed a xenografted tumor of MDA-MB-231 human breast cancer. Native DTX, on the other hand, produced only transient and slight regression of the same tumor xenograft. NC-6301 also significantly inhibited growth of OCUM-2MLN human scirrhous gastric carcinoma in an orthotopic mouse model. Total weight of metastatic lymph nodes was also reduced. In conclusion, NC-6301 with an optimized release rate improved the potency of DTX while reducing its toxicity.